2021
DOI: 10.1002/qre.2924
|View full text |Cite
|
Sign up to set email alerts
|

An extended nonparametric homogeneously weighted moving average sign control chart

Abstract: Parametric (or traditional) control charts are based on the assumption that the quality characteristic of interest follows a specific distribution. However, in many applications, there is a lack of knowledge about the underlying distribution. To this end, nonparametric (or distribution‐free) control charts have been developed in recent years. In this article, a nonparametric double homogeneously weighted moving average (DHWMA) control chart based on the sign statistic is proposed for monitoring the location pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Malela-Majika et al [35] corrected the variance used in the HHWMA X chart design proposed by [51]. For more details regarding the parametric DHWMA and HWMA charts for monitoring the location parameter, readers are referred to Alevizakos et al [22,23,56,65].…”
Section: Joint Location and Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Malela-Majika et al [35] corrected the variance used in the HHWMA X chart design proposed by [51]. For more details regarding the parametric DHWMA and HWMA charts for monitoring the location parameter, readers are referred to Alevizakos et al [22,23,56,65].…”
Section: Joint Location and Scalementioning
confidence: 99%
“…Riaz et al [53] proposed the DHWMA SN chart, which is a reparameterisation of the HWMA SN chart. At the same time, Alevizakos et al [23] mimicked the DEWMA SN chart and proposed the DHWMA SN chart for monitoring shifts in the location parameter. Compared to the HWMA, GWMA, double GWMA (DGWMA), triple exponentially weighted moving average (TWMA) SN charts, and classical DHWMA, it was found that the DHWMA SN chart performs better than the competing charts in many cases, especially for small shifts in the process parameter.…”
Section: Locationmentioning
confidence: 99%